ART AND ENTERTAINMENT IN ISLAM - Muchsin, Misri A (SCAD Independent, 2015)
The implementation of Islamic law, art, and entertainment has gained a various highlight. However, art in Islam have shown its glorious identities and progress. Islam, through its preaching of the main source, Al-Quran, really values the art. Allah has encouraged the people to observe the universe, which is created beautifully and harmoniously. In Aceh, the Council of Indonesian Ulama (MUI) of Aceh Province formed a team or a special committee consisting of 21 experts to arrange a treatise, especially those relating to the art of music, dance and singing. As the result, they had resulted a book published by MUI of Aceh province with the title How Islam Honors Art. The book has examined the art about types and sources in Islam broadly and completely. Consequently, the work of the expert team had led to the placement of the dynamics of art and entertainment in Aceh historical episodes and had brought some influences in the later period.